Atividade pedagógica para o componente curricular de educação física com base em jogo eletrônico - Rech, Gislaine Zanoto (My University, 2023)
This research investigates the extraction of ludic elements from electronic games, situated in the perspective of Digital Culture, as a means to motivate Basic Education students to engage in pedagogical activities of the Physical Education curricular component. Its main objective was to build a pedagogical activity using ludic elements extracted from the electronic game Free Fire™, for the curricular component of Physical Education in Elementary School. The theoretical framework is supported by the Social Interactionist Theory (VIGOTSKY, 2007), as well as on the scientific literature related to Digital Culture, having as main authors Lévy (2007; 2010), Castells (1999; 2003) and Lemos (2002; 2004); for the theme of electronic games, the discussion is supported by Prensky (2010), Carvalho (2016) and Guimarães (2009). In view of the conceptual basis, focused on technological issues, these are related to the propositions of the National Common Curricular Base (BRASIL, 2018), with regard to the Physical Education curricular component (DARIDO; SOUZA JÚNIOR, 2007; DAÓLIO, 2018) and, in particular, to corporal practices and their relationship with the theme of games and activities regarding the object of knowledge of electronic games. This is a qualitative research of documentary constitution, which analyzed the Curricular References of the 27 States of Brazil, based on the BNCC and on the literature of the area, still relying on the technique of Content Analysis, with analytical purpose. From the data analysis, 03 categories emerged from the analytical process and were identified, specifically: 01 - Body in motion; 02 - Use of different electronic devices and 03 - Electronic games. The study evidenced the concern of the States in a) providing opportunities for the educational process contemplating the theme of electronic games in Physical Education with the use of ample body movement; b) enabling access to different electronic devices in the school context; c) considering the use of electronic games in student's daily life for the desired pedagogical intention. At last, it is believed that, from the analysis process, based on the emerging categories, the aforementioned proposal of pedagogical activity presents such aspects, because, when approaching the elements of the corporal practices, in particular, and in a more direct way with the categories 01 and 03, it allows us to understand that ludic elements extracted from Free Fire™ electronic game can represent a possibility to motivate and engage students in body practices, in order to relate electronic game elements to broad body movement. [resumo fornecido pelo autor]
Esta pesquisa investiga acerca da extração de elementos lúdicos de jogos eletrônicos, situados na perspectiva da Cultura Digital, como forma de motivar estudantes da Educação Básica a engajarem-se em atividades pedagógicas do componente curricular de Educação Física. Teve como principal objetivo construir uma atividade pedagógica utilizando elementos lúdicos extraídos do jogo eletrônico Free Fire, para o componente curricular de Educação Física no Ensino Fundamental. O referencial teórico está apoiado na Teoria Sociointeracionista (VIGOTSKY, 2007), assim como na literatura científica relativa à Cultura Digital, tendo como principais autores Lévy (2007; 2010), Castells (1999; 2003) e Lemos (2002; 2004); já acerca da temática de jogos eletrônicos, a discussão é sustentada por Prensky (2010), Carvalho (2016) e Guimarães (2009). Tendo em vista a base conceitual mencionada, voltada às questões tecnológicas, relaciona-se essas às proposições da Base Nacional Comum Curricular (BRASIL, 2018), no que se refere ao componente curricular de Educação Física (DARIDO; SOUZA JÚNIOR, 2007; DAÓLIO, 2018) e, em especial, às práticas corporais e sua relação com a temática dos jogos e das brincadeiras no que se refere ao objeto de conhecimento dos jogos eletrônicos. Esta é uma pesquisa qualitativa de constituição documental, que analisou os Referenciais Curriculares dos 27 Estados do Brasil, com base na BNCC e na literatura da área, apoiando-se ainda na técnica da Análise de Conteúdo, com finalidade analítica. A partir da análise de dados foram identificadas 03 categorias que emergiram do processo analítico, a saber: 01 - Corpo em movimento; 02 - Uso de diferentes dispositivos eletrônicos e 03 Jogos eletrônicos. O estudo evidenciou a preocupação dos Estados em: a) oportunizar o processo educativo contemplando a temática dos jogos eletrônicos na Educação Física com uso de movimento corporal amplo; b) possibilitar o acesso a diferentes dispositivos eletrônicos no contexto escolar; c) considerar o uso de jogos eletrônicos do cotidiano do estudante para a intencionalidade pedagógica desejada. Por fim, acredita se que, a partir do processo de análise, com base nas categorias emergentes, a referida atividade pedagógica apresenta tais aspectos, porque, ao abordar os elementos das práticas corporais, em especial, de maneira mais direta com as categorias 01 e 03, permite compreender que elementos lúdicos extraídos do jogo eletrônico Free Fire podem representar uma possibilidade de motivar e engajar os estudantes em práticas corporais, de modo a relacionar elementos do jogo eletrônico ao movimento corporal amplo. [resumo fornecido pelo autor]
Keywords: Educação; Jogos eletrônicos; Base Nacional Comum Curricular; Educação física; Education; Electronic games; Common National Curriculum Base; Physical education and training